Biologia reprodutiva de duas espécies de Rubiaceae de mata de galeria do Triângulo Mineiro-MG - Consolaro, Hélder Nagai (2004)
Rubiaceae is the largest family with distylous species among the Angiosperms. This floral polymorphism may vary in form and degree leading to homostyly, monomorphism and dioecy, either in populations of the same species or between species of typically distylous genera. The objective of this study was to know the floral biology, including pollination and breeding systems of two Rubiaceae species common in gallery forest of Triângulo Mineiro, MG. Psychotria carthagenensis Jacq. and Manettia cordifolia Mart.. The study was carried out in The Panga Ecological Station and riverside of the Uberabinha (Uberlândia, MG), and complemented with observations of botanic material deposited in herbaria of the region. P. carthagenensis is a understory shrub with small, bee pollinated white flowers. The specie is clearly distylous with two markedly different morphs and reciprocal herkogamy. However, the studied population showed a large deviation from isoplethy (149 pin individuals and only one thrum), alongside self-compatibility condition. Data of herbaria and observations in other area of forest indicated that others populations may show isplethy or dominance of the pin morph, of form that monostyly is a characteristic of isolate populations and not of the specie in general. M. cordifolia is a vine with flowers characteristics typical of hummingbird pollination syndrome, such as red tubular corolla, abundant nectar and absence of odor. The main pollinator was the hummingbird Phaetornis pretrei. The plant cannot be considered a typically distylous specie, although it is in a genera known as distylous. The observed characteristics indicate a specie with pin-monomorphy, probably derived of a distylous ancestral. Controlled pollinations showed a self-incompatible and non-apomictic species. In general, variations in heterostylous characteristics can be associated with different factors but are result of either a crossing-over inside the supergene that controls the distyly or vegetative growth. In ecological terms, the pin morph may have selective advantages over the thrum morph, given the exsert position of the stigma; creating an asymmetry on the pollen flow towards the pin morph. These advantages associated with selfcompatibility may result in pin-monomorphic populations or even give rise to monostylous species in distylous groups. It is important to notice that although the species studied here may be seen as stages in this process, Manettia cordifolia has acquired, possibly anew, a self-sterility mechanism. The absence of information on the distyly genetic control in the Rubiaceae family makes difficult to interpret the variations observed on the present study. Information on the geographic distribution and phylogeny of the groups would be helpful to understand the situation of the species and the origin of these characteristics.